Intervertebral disc cell chondroptosis elicits neutrophil response in Staphylococcus aureus spondylodiscitis - Schweizer, Tiziano A.; Andreoni, Federica; Acevedo, Claudio; Scheier, Thomas C.; Heggli, Irina; Maggio, Ewerton Marques; Eberhard, Nadia; Brugger, Silvio D.; Dudli, Stefan; Zinkernagel, Annelies S. (Frontiers in Immunology, 2022)
To understand the pathophysiology of spondylodiscitis due to Staphylococcus aureus, an emerging infectious disease of the intervertebral disc (IVD) and vertebral body with a high complication rate, we combined clinical insights and experimental approaches. Clinical data and histological material of nine patients suffering from S. aureus spondylodiscitis were retrospectively collected at a single center. To mirror the clinical findings experimentally, we developed a novel porcine ex vivo model mimicking acute S. aureus spondylodiscitis and assessed the interaction between S. aureus and IVD cells within their native environment. In addition, the inflammatory features underlying this interaction were assessed in primary human IVD cells. Finally, mirroring the clinical findings, we assessed primary human neutrophils for their ability to respond to secreted inflammatory modulators of IVD cells upon S. aureus challenge. Acute S. aureus spondylodiscitis in patients was characterized by tissue necrosis and neutrophil infiltration. Additionally, the presence of empty IVD cells’ lacunae was observed. This was mirrored in the ex vivo porcine model, where S. aureus induced extensive IVD cell death, leading to empty lacunae. Concomitant engagement of the apoptotic and pyroptotic cell death pathways was observed in primary human IVD cells, resulting in cytokine release. Among the released cytokines, functionally intact neutrophil-priming as well as broad pro- and anti-inflammatory cytokines known for their involvement in IVD degeneration were found. In patients as well as ex vivo in a novel porcine model, S. aureus spondylodiscitis infection caused IVD cell death, resulting in empty lacunae, which was accompanied by release of inflammatory markers and recruitment of neutrophils. These findings offer valuable insights into the important role of inflammatory IVD cell death during spondylodiscitis and potential future therapeutic approaches.